2015
DOI: 10.1016/j.jvs.2015.03.035
|View full text |Cite
|
Sign up to set email alerts
|

Results of complex aortic stent grafting of abdominal aortic aneurysms stratified according to the proximal landing zone using the Society for Vascular Surgery classification

Abstract: We have shown that the extent of the aneurysm repair as determined by the proximal sealing zone is associated with outcome. Mortality, operative duration, blood loss, and hospital stay all significantly increased as the zones ascended. These data also validate the use of the proposed new classification based on aortic anatomy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
19
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 20 publications
1
19
0
Order By: Relevance
“…Sveinsson et al 12 reported outcomes in 288 patients from Malmö and Lille and concluded that a more complicated stent graft design did not lead to increased risk for perioperative mortality, as confirmed by our study. In contrast, Patel et al, 5 in a study of 150 patients, showed that operative mortality increased significantly with a more proximal landing zone with complex stent graft configuration.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…Sveinsson et al 12 reported outcomes in 288 patients from Malmö and Lille and concluded that a more complicated stent graft design did not lead to increased risk for perioperative mortality, as confirmed by our study. In contrast, Patel et al, 5 in a study of 150 patients, showed that operative mortality increased significantly with a more proximal landing zone with complex stent graft configuration.…”
Section: Discussionmentioning
confidence: 88%
“…The complexity may result in higher perioperative mortality and morbidity as a result of the longer operative time, prolonged catheter and wire manipulations, increased blood loss, increased contrast use, and increased coverage of segmental arteries and associated spinal cord ischemia (SCI). 5 The present study investigated whether stent graft design complexity affects perioperative outcomes of FEVAR in a high-volume endovascular center.…”
mentioning
confidence: 99%
“…Some authors include type IV TAAAs in the statistical analysis as well as patients treated with branched stent-grafts. 2,8 Furthermore, there is a lack of consensus regarding how to classify JAAs and SAAs and the subsequent extent of repair. Result stratification has been carried out according to several different standards, with other authors comparing renal-only fenestrations to more complex designs, while others apply the aneurysm zone classification or the Society for Vascular Surgery/American Association for Vascular Surgery anatomical severity score.…”
Section: Discussionmentioning
confidence: 99%
“…Result stratification has been carried out according to several different standards, with other authors comparing renal-only fenestrations to more complex designs, while others apply the aneurysm zone classification or the Society for Vascular Surgery/American Association for Vascular Surgery anatomical severity score. [7][8][9] It is our belief that stratification of FEVAR results in the abdominal aorta should be limited to abdominal aortic pathology. The current series compared solely patients with JAAs and SAAs excluding patients with TAAAs.…”
Section: Discussionmentioning
confidence: 99%
“…85 Series from referral centers have included between 45 and 607 patients, with 117-1907 target vessels. 5,10,29,[32][33][34]39,80,97 Up to July 2012, a total of 2463 target vessels have been accessed through fenestrations and/or scallops, all within the use of the fenestrated Zenith SG. 20 Overall, early target vessel patency rate ranges from 90.5% to 99.7%.…”
Section: Target Vessel Stenosis/occlusionmentioning
confidence: 99%